The repercussions of the French settlement policy on the inhabitants of rural Mila during the 19th century - Boudouira, Hayat (Milev Journal of Research and Studies, 2017)
The topic of the land property is one of the most important topics, which is still an important theme of discussion in our country side of citizens and they are the sides which I aimed to show in mila fringes which belong the internal plains region. As it is characterized with the natural varieties and the historical richness. These factors played a big role in the lands (fields) owning repartitions during the Othman (Turkish) period. An ethnical separation of private properties which was linked to a social building / formation: the tribes of ferdjioua, Zeghaia, Ouled Kebab, beni Meroine, OuledBouslah. Some of them were favorised to work on the land (as farmers in the lands/fields). The tribe of Ouled Kebab in addition to some other tribes stagnented and fixed in the montagnious regions with the (Arab owning) This stability gave them a type independence but in contradiction they didn’t flee from the yearlywaves of recensements to extract taxation. This lead to the shift of the lands from the ( Arche owners to the ( Beylik / state) : this is the case of the tribe of zouagha ; This relationship appears in the relationship between the owning/properties and the vanishing families. Ouled Ben Achour, and Ibn Azeddine, through its cutting of the separated lands to get some special services, this caused the new aspects of the private properties.So special royal land marks this situation martial associated structurehave undergone a series of transformations and changes during the 19th century As a result of privacy of heavily estate arsenal of laws notably the laws of senates knonsolt 1863 until 1897 the last real estate laws issued by the trench legislature which would create a disjoined social sons and sons create civil harrow billable centers housing properties estate and wide belonging to the longevity of Europeans